Resolving Auditory Neuropathy Spectrum Disorder in a Case with Leigh’s Disease - Pradeep Yuvaraj; Anjana Thomas; Alphy Sabu; Jayaram Mannarukrishnaiah (Journal of All India Institute of Speech and Hearing, 1970)
Leigh's Disease is a rare inherited neuro-metabolic disorder that aects the central nervous system in infants and children. The disorder is characterized by progressive neurologic deterioration. Patients with Leigh syndrome show inconsistent or absent ABR and abnormal interpeak latencies. Auditory neuropathy spectrum disorder has also been reported. Master PM, 2.8 years old, 2nd born to non-consanguineous parents was brought to our department with the complaints of inconsistent response to auditory stimuli and regression of developmental milestones including that of speech-language. MRI brain showed bilateral T2 FLAIR hyper intense signal changes in several sub-cortical regions of the brain including basal ganglia. ABR results showed ringing cochlear microphonics up to 60dB nHL in both the ears. ABR showed presence of 5th peak up to 70dB nHL in the right ear and 60dB nHL in the left ear. Oto-acoustic emissions were present in both the ears. Based on the results of audiological evaluation and improvement shown by PM in speech-language  following neurological intervention, it is speculated that PM may have had a transient form of ANSD during his development.